EXPRESSION OF BAP1 IN CLEAR CELL RENAL CELL CARCINOMA - Fatima, Arooj; Mushtaq, Sajid; Loya, Asif; Hassan, Usman; Sheikh, Umer Nisar (Journal of Ayub Medical College Abbottabad, 2022)
Background: BAP1 (BRCA1 associated protein 1 on chromosome 3) is a commonly mutated gene in clear cell renal cell carcinoma. Aim of the study was to evaluate the prognostic significance of BAP1 by immunohistochemistry in clear cell renal cell carcinoma. Methods: It was a descriptive case series in which data was retrospectively collected. Immunohistochemistry was used to evaluate the loss of nuclear expression of BAP1. Results: Loss of BAP1 was observed in 60% of cases of clear cell renal cell carcinoma. 27% of grade 1 tumours, 62% of grade 2 tumours, 65% of grade 3 tumours and 66% of grade 4 tumours showed loss of BAP1. Loss of BAP1 was observed in 54% cases of stage 1 tumours, 72% of stage 2 tumours and 66% of stage 3 tumours. Our study showed loss of BAP1 in 67% of cases with tumour necrosis, in 75% of cases with sarcomatoid features and in 60% of patients with distant metastasis. Conclusions: We conclude that the loss of BAP1 nuclear expression is associated with poor prognostic features. i.e., higher grade, higher stage, tumour necrosis, sarcomatoid features and distant metastasis leading to death of patients.